Explosion and health hazards caused by dust during coal mining and their prevention strategies - Muhammad Imran Rashid; Muhammad Athar; Muhammad Waqas Iqbal; Hafiz Khurram Shahzad; Ayesha Mobeen; Mahnoor Asif (Discover Chemical Engineering)
Abstract The world’s energy supplies depend on a scale of high significance upon the coal industry. Nevertheless, as with any other case, some safety issues require urgent response, for example, coal dust explosion accidents. A total of one hundred and six coal dust explosions during mining, particularly in China, were reported during past 60 years. Coal dust also cause deleterious health effects, causing multiple diseases such as pneumoconiosis, chronic obstructive pulmonary disease (COPD), rhinitis, asthma, extrinsic allergic alveolite (EAA), fibrosing alveolitis, cancers, heart disease, visual disturbances namely cataract formation and irritation, skin problems and many more. Dust hazard analysis (DHA) methodology, dust control, dust accidents and much more is covered in this article. A literature analysis on dust explosion hazards during coal mining has been presented in this work that depicts, that most of the literature covers dust hazards of coal mining industry. A guideline regarding enhancement of safety during coal mining is presented in this work both to avoid the dust explosion scenarios and adverse health impacts of coal dust that might be helpful for coal mining industries.